STRATEGI BADAN PENDAPATAN DAERAH KABUPATEN BUTON TENGAH DALAM UPAYA PENINGKATAN PENDAPATAN DAERAH - Samiun; Muh. Amir; Dwi Putranto Riau (Journal Publicuho, 2024)
This study aims to analyze the Regional Revenue Agency (BAPENDA) planning strategies of Buton Tengah Regency in increasing regional income. Using a qualitative approach, the study involved 20 respondents selected through a PSS (5:1) mechanism and 5 informants chosen purposively. Data collection was conducted through a series of in-depth interviews to evaluate organizational performance based on five key dimensions: productive efficiency, service standards, responsiveness, compliance level, and management transparency. Data analysis employed the interactive approach developed by Milles and Huberman. The findings indicate that the performance of BAPENDA Buton Tengah is rated as "satisfactory" when assessed across these five dimensions. To enhance regional revenue, BAPENDA implements tax planning strategies to maintain tax burdens at an optimal level, allowing companies or individuals to meet tax obligations while maximizing financial benefits or efficiency. Generally, the ideal tax planning percentage for Buton Tengah is measured by Tax Revenue Efficiency (a minimum of 20%-25% of total PAD) and a balanced Tax Ratio in the range of approximately 10%-15%, depending on the main economic sectors of Buton Tengah.